Negative regulation of inducible nitric-oxide synthase expression mediated through transforming growth factor-beta-dependent modulation of transcription factor TCF11 - Berg, David T; Gupta, Akanksha; Richardson, Mark A; O'Brien, Lee A; Calnek, David; Grinnell, Brian W (The Journal of biological chemistry, 2007)
Inducible nitric-oxide synthase (iNOS) plays a central role in the regulation of vascular function and response to injury. A central mediator controlling iNOS expression is transforming growth factor-beta (TGF-beta), which represses its expression through a mechanism that is poorly understood. We have identified a binding site in the iNOS promoter that interacts with the nuclear heterodimer TCF11/MafG using chromatin immunoprecipitation and mutation analyses. We demonstrate that binding at this site acts to repress the induction of iNOS gene expression by cytokines. We show that this repressor is induced by TGF-beta1 and by Smad6-short, which enhances TGF-beta signaling. In contrast, the up-regulation of TCF11/MafG binding could be suppressed by overexpression of the TGF-beta inhibitor Smad7, and a small interfering RNA to TCF11 blocked the suppression of iNOS by TGF-beta. The binding of TCF11/MafG to the iNOS promoter could be enhanced by phorbol 12-myristate 13-acetate and suppressed by the protein kinase C inhibitor staurosporine. Moreover, the induction of TCF11/MafG binding by TGF-beta and Smad6-short could be blocked by staurosporine, and the effect of TGF-beta was blocked by the selective protein kinase C inhibitor calphostin C. Consistent with the in vitro data, we found suppression of TCF11 coincident with iNOS up-regulation in a rat model of endotoxemia, and we observed a highly significant negative correlation between TCF11 and nitric oxide production. Furthermore, treatment with activated protein C, a serine protease effective in septic shock, blocked the down-regulation of TCF11 and suppressed endotoxin-induced iNOS. Overall, our results demonstrate a novel mechanism by which iNOS expression is regulated in the context of inflammatory activation.